2004
DOI: 10.1128/aem.70.1.356-362.2004
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Genes Associated with Enterotoxigenic and Enterohemorrhagic Escherichia coli in Agricultural Waste Lagoons

Abstract: The prevalence among all Escherichia coli bacteria of the LTIIa toxin gene and STII toxin gene, both associated with enterotoxigenic E. coli, and of three genes (stxI, stxII, and eaeA) associated with enterohemorrhagic E. coli was determined in farm waste disposal systems seasonally for 1 year. Single-and nested-PCR results for the number of E. coli isolates carrying each toxin gene trait were compared with a five-replicate most-probable-number (MPN) method. The STII and LTIIa toxin genes were present continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…The presence of E. coli strains with VG profiles similar to EHEC (21), EPEC (3,19), and ETEC (21) have been reported previously in the fresh and estuarine waters. However, the distribution of diarrheagenic E. coli pathotypes in freshwater, especially after storm events, still remains relatively unknown.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of E. coli strains with VG profiles similar to EHEC (21), EPEC (3,19), and ETEC (21) have been reported previously in the fresh and estuarine waters. However, the distribution of diarrheagenic E. coli pathotypes in freshwater, especially after storm events, still remains relatively unknown.…”
mentioning
confidence: 90%
“…Despite increasing evidence that E. coli strains originating from human and animal feces contain several VGs (2,16,18), only a few studies have determined whether E. coli strains isolated from fresh and marine water contain VGs and are potentially pathogenic (3,(19)(20)(21). The presence of E. coli strains with VG profiles similar to EHEC (21), EPEC (3,19), and ETEC (21) have been reported previously in the fresh and estuarine waters.…”
mentioning
confidence: 98%
“…These methods are useful for identification and tracking E. coli O157:H7 and other E. coli strains from different sources (19,35); however, they do not assess the pathogenic potential of the strains. Research has shown that the prevalence of potentially virulent E. coli strains or their associated genes may in the environment may be greater than previously realized (9)(10)(11). However, none of these studies tested the virulence potential of environmental bacteria carrying these genes.…”
mentioning
confidence: 91%
“…In this context, specific virotypes can tentatively be ascribed to environmental isolates on the basis of virulence gene profiling, the assumption being that specific complements of virulence genes are associated with the ability to cause specific diseases (6)(7)(8). The virulence gene profiling approach has been used to characterize the seasonal and spatial distribution of waterborne E. coli that are potentially pathogenic to humans or livestock and to identify associations in virotype distribution within catchments with variation in land use, climate, and the distribution of potential sources of fecal contamination (9)(10)(11)(12)(13)(14)(15). There are, however, practical problems with the tractability of the virulence gene profiling approach.…”
mentioning
confidence: 99%